Local Multipliers and Human Capital in the US and Sweden - Enrico Moretti; Per Thulin (Research Institute of Industrial Economics (IFN), 2012)
We show that every time a local economy generates a new job by attracting a new business in the traded sector, a significant number of additional jobs are created in the non-traded sector. This multiplier effect is particularly large for jobs with high levels of human capital and for high tech industries. These findings are important for local development policies, as they suggest that in order to increase local employment levels, municipalities should target high tech employers with high levels of human capital.
Keywords: J23; R11; R12; R23; 330; Local multipliers; Local labor markets; Labor demand; Regionaler Arbeitsmarkt; Arbeitsnachfrage; Hochtechnologiesektor; Hochqualifizierte Arbeitskräfte; Schweden; USA